Pharmacokinetic Assessment of Drug Efflux from Erythrocytes Loaded with Corticosteroid Esters - Jusko, William J.; Yu, Ruihong (Pharmaceutical research, 2025)
Purpose Drugs can be found in erythrocytes (RBC) in accordance with their physicochemical and specific binding properties, but particularly high concentrations can be attained using an ex vivo hypotonic pre-swelling method. Pharmacokinetic (PK) methodology and characterization of in vivo data for RBC-loaded corticosteroid prodrugs was sought. Methods Three studies providing in vitro and in vivo assessments of the pharmacokinetics of steroid ester prodrugs loaded into RBC were found. A PK model involving three fractional input rates and two-compartment disposition was applied. Results After their sodium phosphate ester pro-drugs were loaded into RBC and dosed intravenously, dexamethasone (DEX) and betamethasone (BET) plasma concentrations were markedly prolonged with three phases in humans and animals. For DEX in humans, a PK model accounted for the typical biexponential disposition of the active steroid and for input of a large fraction (0.72) released within 1 h, a small fraction (0.27) released over several hours ( t 1/2 = 5.5 h), and a very small fraction (0.008) released extremely slowly ( t 1/2 = 109 h). The DEX RBC concentrations were expected to remain far higher than plasma concentrations for this prolonged time. The PK model was also applied to DEX in rabbits and BET in rats with generally similar results and indicating full bioavailability. Conclusions The proposed PK methodology well characterized the input properties of RBC-loaded controlled-release formulations of corticosteroids in animal and humans in context of the flip-flop kinetics of the released drug. The model may be relevant to other types of RBC-loaded therapeutic agents. Graphical Abstract